2007
DOI: 10.3354/meps334001
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular acid–base regulation during short-term hypercapnia is effective in a shallow-water crab, but ineffective in a deep-sea crab

Abstract: Rising levels of atmospheric carbon dioxide could be curbed by large-scale sequestration of CO 2 in the deep sea. Such a solution requires prior assessment of the impact of hypercapnic, acidic seawater on deep-sea fauna. Laboratory studies were conducted to assess the short-term hypercapnic tolerance of the deep-sea Tanner crab Chionoecetes tanneri, collected from 1000 m depth in Monterey Canyon off the coast of central California, USA. Hemolymph acidbase parameters were monitored over 24 h of exposure to seaw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
137
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(144 citation statements)
references
References 49 publications
5
137
1
Order By: Relevance
“…18,19), with the hypothesis being that organisms will have more effective mechanisms to cope with stress if they frequently experience a more variable environment. One example of this hypothesis for pelagic zooplankton comes from knowledge of mesozooplankton (20) distributions in relation to oxygen minimum zones (OMZs), and thus their sensitivity to low oxygen (20).…”
Section: Significancementioning
confidence: 99%
“…18,19), with the hypothesis being that organisms will have more effective mechanisms to cope with stress if they frequently experience a more variable environment. One example of this hypothesis for pelagic zooplankton comes from knowledge of mesozooplankton (20) distributions in relation to oxygen minimum zones (OMZs), and thus their sensitivity to low oxygen (20).…”
Section: Significancementioning
confidence: 99%
“…20,21 Studies using decapod crustaceans demonstrated that these invertebrates can also fully compensate hypercapnia induced pH e disturbances through active bicarbonate accumulation in body fluids. [22][23][24][25] For example, in response to 1 kPa water pCO 2 Cancer magister increased its blood [HCO 3 ¡ ] by 12 mM within 24 h to fully compensate pH e . 25 Studies on Carcinus maenas and Callinectes sapidus also indicated comparable high acid-base regulatory abilities.…”
Section: Acid-base Physiology In Marine Vertebrates and Invertebratesmentioning
confidence: 99%
“…[22][23][24][25] For example, in response to 1 kPa water pCO 2 Cancer magister increased its blood [HCO 3 ¡ ] by 12 mM within 24 h to fully compensate pH e . 25 Studies on Carcinus maenas and Callinectes sapidus also indicated comparable high acid-base regulatory abilities. [26][27][28][29] Although less active marine invertebrates were generally shown to have lower capabilities to compensate for extracellular acid-base disturbances, some echinoderms including sea urchins (Strongylocentrotus droebachiensis) and brittle stars (Amphiura filiformis) were demonstrated to be able to control extracellular pH to a certain degree.…”
Section: Acid-base Physiology In Marine Vertebrates and Invertebratesmentioning
confidence: 99%
“…Samples of PCF were drawn anaerobically through the oral membrane into ice-cold gas-tight Hamilton syringes rinsed with a modified Crab Ringer comprised of NaCl (460 mM), KCl (10 mM), CaCl 2 (20 mM), MgCl 2 (9.5 mM), adjusted to pH 7.8 (Lang and Gainer, 1969;Pane and Barry, 2007). Fluid samples were then centrifuged aerobically at 4000 × g at 5 • C for 1 min to remove debris, added (200 µL) to round-bottom flasks for equilibration with humidified gas mixtures of CO 2 and nitrogen from preanalyzed cylinders (Airgas), and allowed to equilibrate for 90 min in a shaking cooler at 5 • C. Samples were then drawn into gas-tight syringes and pH (total scale) was measured using a microelectrode and in-line reference electrode (Microelectrodes) thermostatted to 5 • C and coupled to an Accumet (Fisher Scientific) pH meter.…”
Section: Pcf Buffering Capacitymentioning
confidence: 99%
“…The high amount of genetic diversity and/or plasticity presumably required for a population to persist throughout a bathymetric range including an OMZ suggests we should expect fairly high tolerance to at least the extent of conditions seen within its bathymetric range. We expect the apparent limitation in tolerance of OMZ taxa to global climate change is not a product of evolutionary constancy, but rather is a product of the limited energy (food and oxygen) available to cope with the stress of environmental change (Barry et al, 2011;Pane and Barry, 2007;Seibel and Walsh, 2003). Taking these considerations into account, we aim to investigate the physiological effects of elevated pCO 2 on a calcifying OMZ taxon, the deep-sea fragile urchin Strongylocentrotus fragilis.…”
Section: Introductionmentioning
confidence: 99%